Plant but not animal sourced nitrate intake is associated with lower dementia-related mortality in the Australian Diabetes, Obesity, and Lifestyle Study - Rajendra, Anjana; Bondonno, Nicola P.; Zhong, Liezhou; Radavelli-Bagatini, Simone; Murray, Kevin; Rainey-Smith, Stephanie R.; Gardener, Samantha L.; Blekkenhorst, Lauren C.; Magliano, Dianna J.; Shaw, Jonathan E.; Daly, Robin M.; Anstey, Kaarin J.; et al. (Frontiers in Nutrition, 2024)
Introduction: Dietary nitrate is potentially beneficial for cardiovascular, cerebrovascular, and nervous systems due to its role as a nitric oxide (NO) precursor. Increased nitrate intake improves cardiovascular health and therefore could protect against dementia, given the cardiovascular-dementia link.Objective: To investigate the association between source-dependent nitrate intake and dementiarelated mortality. As individuals with diabetes are at higher risk of dementia, a secondary aim was to investigate if the associations between nitrate and dementia varied by diabetes mellitus (DM) and pre-diabetes status.Methods: This study involved 9,149 participants aged ≥25 years from the well-characterized Australian Diabetes, Obesity, and Lifestyle (AusDiab) Study followed over a period of 17 years.Intakes of plant-sourced, vegetable-sourced, naturally occurring animal-sourced nitrate, and processed meat (where nitrate is an allowed additive)-sourced nitrate were assessed from a 74item food frequency questionnaire completed by participants at baseline and nitrate databases were used to estimate nitrate from these different dietary sources. Associations between sourcedependent nitrate intake and dementia-related mortality were assessed using multivariableadjusted Cox proportional hazards models adjusted for demographics, lifestyle, and dietary factors.Results: Over 17 years of follow-up, 93 (1.0%) dementia-related deaths occurred of 1,237 (13.5%) total deaths. In multivariable-adjusted models, participants with the highest intakes of plant-sourced nitrate (median intake 98 mg/d) had a 57% lower risk of dementia-related mortality [HR (95% CI): 0.43 (0.22, 0.87)] compared to participants with lowest intakes of plantsourced nitrate (median intake 35 mg/d). A 66% lower risk was also seen for higher intakes of vegetable-sourced nitrate [HR (95% CI): 0.34 (0.17, 0.66)]. No association was observed for animal-sourced nitrate, but the risk was two times higher among those who consumed the most processed meat-sourced nitrate intake [HR (95%): 2.10 (1.07, 4.12)]. The highest intake of vegetable-sourced nitrate was associated with a lower risk of dementia-related mortality for those with and without DM and pre-diabetes.Encouraging the intake of nitrate-rich vegetables, such as green leafy vegetables and beetroot, may lower the risk of dementia-related mortality, particularly in individuals with (pre-) diabetes who are at a higher dementia risk.